Profiling teachers' readiness for online teaching and learning in higher education: Who's ready?. (May 2021) - Scherer, Ronny; Howard, Sarah K.; Tondeur, Jo; Siddiq, Fazilat
Abstract: The COVID-19 pandemic has forced a shift to online teaching and learning (OTL) in colleges and universities across the globe, requiring teachers to adapt their teaching in a very short time—independent of whether they were prepared. Drawing from an international sample of N  = 739 higher education teachers in 58 countries, the present study sheds light on teachers' readiness for OTL at the time of the pandemic by (a) identifying teacher profiles based on a set of key dimensions of readiness; (b) explaining profile membership by individual teacher characteristics, contextual aspects of the shift to OTL, and country-level indicators representing educational innovation and cultural orientation. We conducted latent profile analysis and identified three teacher profiles with consistently high or low readiness or an inconsistent readiness profile—hence, teachers in higher education are not a homogeneous group. Importantly, key individual and contextual variables, such as teachers' gender and prior OTL experience, the context of the OTL shift, the innovation potential in education, and cultural orientation, explained profile membership. We discuss these findings with respect to the nature of the profiles, how they can be understood with respect to key determinants, and their implications for OTL in higher education. Highlights: Teachers' readiness for OTL (Online Teaching and Learning) is multifaceted. Three readiness profiles existed (high, low, and inconsistent readiness). Gender, prior experience, and OTL preparation explained profile membership. Countries ready for OTL avoided uncertainty and were long-term oriented. Innovation and culture explained profile membership across countries.